Components influencing consumers in choosing hospital - SHREE, MS K.C. RAJA; MR JAYASURIYAA R (The journal of contemporary issues in business and government, 2020)
The main reason of this study is to determine the relationship between the Consumer and choosing Hospital in the Indian Healthcare Industry and to know about Factors Influencing Consumers in Choosing Hospital. This paper studies factors influencing consumer’s perception towards Choosing Hospital. The study is made on a descriptive basis and the primary data is collected from Patients. The data is collected on probability basis from 108 respondents and is analyzed with the SPSS tool .The collected data were classified, tabulated and analyzed with statistical tools Frequency analysis, Mean analysis. Results express the majority of respondents were female and of age majority were Less than 25. The need of the study is to Access the factors that influence behaviour of the consumers towards choosing the hospital, to access the facilities from medical centres to access needed consumers in specific medical service, it is used to identify patient reference in choosing the hospital and to analyse the factors that are considered by consumers while choosing hospital. The objective is to find out factors influencing consumers in choosing hospital, to calculate factorization of factors influencing consumers in choosing hospital and to find out difference between demographic variables and factors influencing consumers in choosing hospital. It is found that choosing a hospital is influenced by Hospital preference, Timing preference and treatment preference and there is no significant difference between Hospital preference, Timing preference and treatment preference. Innovations implemented in hospitals also play a major role in hospital choice.